DETEKSI DINI DEPRESI MAHASISWA BARU JURUSAN KEPERAWATAN - LOTULUNG, CHRISTA VIKE; PURNAWINADI, I GEDE (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2024)
Depression is a significant mental health problem among students, including nursing students. Nursing students face high academic pressure, the demands of clinical practice, and emotional burdens that can increase the risk of depression. This study aims to identify the level of depression in new students majoring in nursing as a first step to support early detection. The research used a quantitative descriptive design with total sampling technique. The number of samples involved in this research were 199 new students in one of the nursing study programs in North Sulawesi. Data were collected using the PHQ-9 and analyzed using descriptive statistical techniques to explain the distribution of depression levels of new students majoring in nursing. The results of the analysis provide an overview of the prevalence of depression and the level of severity experienced by students. Early detection of depression in nursing students is an important step in maintaining mental health. It is hoped that this research can contribute to increasing attention to mental health problems in the academic environment, especially among nursing students. This research has the potential to influence the policies of educational institutions in providing appropriate resources and support for nursing students to overcome the challenges faced during their education. ABSTRAKDepresi merupakan masalah kesehatan mental yang signifikan di kalangan mahasiswa, termasuk mahasiswa jurusan keperawatan. Mahasiswa keperawatan menghadapi tekanan akademis yang tinggi, tuntutan praktik klinis, serta beban emosional yang dapat meningkatkan risiko depresi. Penelitian ini bertujuan untuk mengidentifikasi tingkat depresi pada mahasiswa baru jurusan keperawatan sebagai langkah awal untuk mendukung deteksi dini. Penelitian menggunakan desain deskriptif jenis kuantitatif dengan teknik total sampling. Jumlah sampel yang terlibat dalam penelitian ini adalah 199 mahasiswa baru di salah satu program studi keperawatan di Sulawesi Utara. Data dikumpulkan mengguanan PHQ-9 dan dianalisis menggunakan teknik statistik deskriptif untuk menjelaskan distribusi tingkat depresi mahasiswa baru jurusan keperawatan. Hasil analisis memberikan gambaran tentang prevalensi depresi dan tingkat keparahan yag dialamai mahasiswa. Deteksi dini depresi pada mahasiswa keperawatan sebagai langkah penting dalam menjaga kesehatan mental. Penelitian ini diharapkan dapat memberikan kontribusi dalam peningkatan perhatian terhadap masalah kesehatan mental di lingkungan akademik, khususnya di kalangan mahasiswa jurusan keperawatan. Penelitian ini memiliki potensi untuk mempengaruhi kebijakan institusi pendidikan dalam menyediakan sumber daya dan dukungan yang tepat bagi mahasiswa keperawatan agar dapat mengatasi tantangan yang dihadapi selama masa pendidikan.